POTENSI PERTUMBUHAN MERANTI DI AREAL BEKAS TEBANGAN DENGAN SISTEM SILVIKULTUR TEBANG PILIH TANAM JALUR (TPTJ) DI PT. SUKA JAYA MAKMUR KABUPATEN KETAPANG KALIMANTAN BARAT - Sari, Dewi Kartika; AM, Iskandar; Hardiansyah, Gusti (JURNAL HUTAN LESTARI, 2013)
The purpose of this study was to determine the increments of the diameter and height of the annual average of Red Meranti trees at different age intervals through the use of silvicultural Selective Cutting and Line Planting (TPTJ) carried out in the logged area of PT . Suka Jaya Makmur in Ketapang Regency of West Kalimantan. The research method applied was a single- plot method that is a method with a sampling plot representing every logged age by measuring the plants diameters and heights in the lane of the logged area of TPTJ line, and the sampling applied was purporsive sampling. The increments of the average diameter growth of Shorea johorensis species in planting forests were smaller than Shorea leprosula and Shorea Shorea parvifolia. Whereas there was no decline or incline in the diameter of that species in the natural forest that was staying in the same value at 0.59 cm/year. The average increments of the diameters of Shorea leprosula, Shorea johorensis, and Shorea parvifolia were 2.23 cm/year, 1.79 cm/year and 1.81 m/year respectively. Moreover, the height average increments of Shorea leprosula in the planting forest was 2,39 m/year and 0,53/year in the natural forest. The average increase in height of Shorea johorensis in planting forest was 1,93 m/year and 0,50 m/year in the natural forest, while for Shorea parvifolia species, there was an average increment of height of 1,92 m/year in planting forest and 0,58 m/year in the natural forest. Keywords: S. johorensis, S. leprosula, S. parvifolia, diameter increment and height increment